Guided bone regeneration with autogenous graft of Chin - Ramos Perfecto, Donald (2007)
The deficiencies of bone quality in the patient, either of wide or height, make the clinician take decisions to improve these conditions, with the purpose of placing implants or improving faulty edges that can support a prosthetics frame. For this, the procedures of guided bone regeneration with ones own chin bone (autogenous implant), are the ones with the best forecast for resolving the problem. In this clinical case we show the diagnosis, the surgical technique, the advantages and pharmacotherapy of guided bone regeneration treatment with autogenous chin implant.